2013
DOI: 10.1128/mbio.00598-13
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy To Estimate Unknown Viral Diversity in Mammals

Abstract: The majority of emerging zoonoses originate in wildlife, and many are caused by viruses. However, there are no rigorous estimates of total viral diversity (here termed “virodiversity”) for any wildlife species, despite the utility of this to future surveillance and control of emerging zoonoses. In this case study, we repeatedly sampled a mammalian wildlife host known to harbor emerging zoonotic pathogens (the Indian Flying Fox, Pteropus giganteus) and used PCR with degenerate viral family-level primers to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
310
0
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(322 citation statements)
references
References 52 publications
(48 reference statements)
3
310
0
9
Order By: Relevance
“…In a recent study aiming at the assessment of viral diversity of mammals, numerous novel viruses including AdVs were found in the Indian flying fox (Pteropus giganteus) (Anthony et al, 2013). The authors described an AdV almost identical to BtAdV-1 (AB303301) (with a single silent mutation on the short pol fragment), which was detected in the closely related species (Ryukyu flying fox, Pteropus dasymallus yayeyamae, Maeda et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study aiming at the assessment of viral diversity of mammals, numerous novel viruses including AdVs were found in the Indian flying fox (Pteropus giganteus) (Anthony et al, 2013). The authors described an AdV almost identical to BtAdV-1 (AB303301) (with a single silent mutation on the short pol fragment), which was detected in the closely related species (Ryukyu flying fox, Pteropus dasymallus yayeyamae, Maeda et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, most bat viruses reported are RNA viruses and were identified by nucleic acid detection. Previously, we and other investigators have demonstrated the high prevalence and great genetic diversity of AdVs in different bat species by PCR screening (Anthony et al, 2013;Casas et al, 2010;Chen et al, 2012;Li et al, 2010;Lima et al, 2013;Vidovszky et al, 2015). Given that over 1000 bat species are known worldwide (Simmons, 2005), the prevalence and number of bat AdV types need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of viral nucleic acid by PCR to identify viruses in bats represents the most common method employed in published studies. Several groups have also used nextgeneration sequencing platforms to identify most, if not all, of the viruses in a target species of bat, termed the 'bat virome' (Anthony et al, 2013;Baker et al, 2013a;Donaldson et al, 2010;Ge et al, 2012;Li et al, 2010). However, determining the zoonotic and pathogenic potential of these agents is very difficult based on sequence information alone.…”
mentioning
confidence: 99%